Addendum: Hussein et al. The modified Gompertz model demonstrates a variable growth rate between two Centella asiatica phenotypes. Journal of Biochemistry, Microbiology and Biotechnology, 2017, Vol 5, No 1, 18-20. (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
The Acknowledgement section (p.20) has been left out, and it should be added as follows. Acknowledgment The study is funded by the Ministry of Higher Education, Malaysia, under the Exploratory Research Grant Scheme (ERGS) [ERGS/1/2012/SKK10/IMU/03/4].